Dominasi Scholar Academic dalam Kurikulum Pesantren: Studi Ideologi Kurikulum Pendidikan Islam Perspektif Michael Schiro - Rosyid, Muhammad Iqbal; Adibuddin, Muhammad Nur; Muzakky, Ahmad Faid; Nugroho, Muhamad Yusuf Amin (Paedagogie, 2026)
This study aims to examine the dominance of the Scholar Academic ideology in the pesantren curriculum through the perspective of Michael Schiro. This study employs a descriptive qualitative approach using library research. The research data were obtained from primary and secondary literature discussing curriculum ideology, pesantren education, kitab kuning, the authority of kiai, learning methods, and santri evaluation. Data were collected through the tracing, selection, and critical review of relevant scholarly sources. Furthermore, the data were analyzed using directed qualitative content analysis by referring to Schiro’s four categories of curriculum ideology, namely Scholar Academic, Social Efficiency, Learner Centered, and Social Reconstruction. The findings indicate that the pesantren curriculum has a strong tendency toward Scholar Academic. This tendency is reflected in the central position of kitab kuning, the transmission of classical religious knowledge, the scholarly authority of kiai, and an evaluation system based on textual mastery. Nevertheless, this dominance is not rigid, as it still contains humanistic values through the formation of adab, exemplary conduct, khidmah, and santri mentoring. This study concludes that Scholar Academic Pesantren represents a distinctive curriculum orientation that integrates mastery of knowledge, continuity of tradition, and the humanization of santri.